TED talks the official TED guide to public speaking - Anderson, Chris 1957 (Houghton Mifflin Harcourt, 2016)
Since taking over TED in 2001, Chris Anderson has shown how carefully crafted talks can be the key to unlocking empathy, spreading knowledge, and promoting a shared dream. Done right, a talk can electrify a room and transform an audience's worldview; it can be more powerful than anything in written form. This book explains how the miracle of powerful public speaking is achieved, and equips you to give it your best